Subspecificities of anticentromeric protein A antibodies identify systemic sclerosis patients at higher risk of pulmonary vascular disease. Issue 25 (June 2016) - Perosa, Federico; Favoino, Elvira; Favia, Isabella Eleonora; Vettori, Serena; Prete, Marcella; Corrado, Addolorata; Cantatore, Francesco Paolo; Valentini, Gabriele
Abstract : Abstract: Patients with systemic sclerosis (SSc) who express autoantibodies to centromeric proteins (CENPs) are at risk of developing pulmonary vascular disease and pulmonary arterial hypertension without fibrosis. Currently no biomarkers are available to predict these complications. We previously characterized the fine specificity of anti-CENP-A antibodies in SSc by screening a phage display library (expressing random 12-mer peptides), and identified phage clones whose peptides were differentially recognized by patients' autoantibodies. Here, we examined if subgroups of SSc patients with different anti-CENP-A antibody subspecificities also differ clinically, and if serum reactivity to phage-displayed peptides can predict pulmonary vascular disease. Clinical data and serum samples were collected from 84 anti-CENP-A-positive SSc patients. Indirect ELISAs were used to test serum reactivity. Pulmonary vascular disease was defined as high systolic pulmonary arterial pressure (sPAP) and low diffusing lung capacity for carbon monoxide (DLCO; percent of predicted values). Sera were screened for reactivity to peptides expressed by phage clones pc4.2 and pc14.1, confirming our earlier observation of differential specificities. Linear regression showed that the levels of antibodies specific for the 2 phage clones were associated with clinical features of pulmonary vascular disease, but in opposite ways: anti-pc4.2 antibodies were positively associated with sPAP and inversely associated with DLCO, whereas anti-pc14.1 antibodies were inversely associated with sPAP and positively associated with DLCO. Anti-pc4.2 and anti-pc14.1 antibody levels predicted sPAP independently of DLCO. These associations were confirmed by logistic regression using antibodies as predictors and dichotomized sPAP (cutoff, 45 mm Hg) as outcome. The ratio of the 2 antibody levels was a useful marker in predicting high sPAP. This study demonstrates that some SSc clinical features associate with subspecificities of anti-CENP-A antibodies. Moreover, it shows that a simple, inexpensive phage-based assay can predict which SSc patients have high sPAP and low DLCO, hence who are at greater risk of developing pulmonary arterial hypertension. The ability to identify these at-risk patients can contribute to clinical efficiency and effectiveness. Further research into the peptides expressed by the phage clones may reveal the molecular mechanisms that put some anti-CENP-A-positive patients at greater risk than others for pulmonary vascular disease.